The Cold War, 1945-1991 - Mason, John W., 1939- (Lancaster pamphlets., 1996)
Mason provides concise coverage of the Cold War, paying particular attention to the Soviet-American dimension and drawing on the latest research of revisionist scholars. Complex events are clearly explained making this an ideal introductory text.